Development of a New Questionnaire to Assess the Social Impact of Non-communicable Diseases - Ishani Hanspal; Farah Naaz Fathima; Karthik Murali; Abhay Sood; Fathima Ayoob; Tinku Thomas (Indian Journal of Community Medicine)
Background: Non-communicable diseases (NCDs) have a considerable impact on an individual’s social life. Life-long medication, fear of death, dietary restrictions, hospital admissions, dependency on caregivers, and strained interpersonal relationships play a role. The available questionnaires measure only individual aspects of social impact. The aim of the study was to develop and validate a comprehensive questionnaire to assess the social impact of NCDs. Material and Methods: A cross-sectional study was conducted among patients and caregivers seeking care at a tertiary care hospital for diabetes, hypertension, chronic obstructive pulmonary disease (COPD), stroke, coronary artery disease (CAD), and cancer. Thirty patients each with the above diseases were administered Cousineau Self-Perceived Burden Scale to assess perceived burden among patients, Caregiver Burden Scale to assess caregiver burden, EuroQol-5D-3L to assess the quality of life, and face validated questions of sociodemographic details, cost of healthcare, and stress due to disease. Rasch analysis was performed to identify items that lie within the traditional bounds of mean-square item fit. The Delphi method with 10 subject experts was used to identify the questions that would be included in the final tool. Results: The data consists of 150 observations, with 77 categorical questions subdivided into various domains. From this, a total of 30 questions were extracted by Rasch analysis. The new questionnaire had good internal consistency (Cronbach’s alpha: 0.969, 95% confidence interval: 0.96–0.98). The questionnaire was finalized after reaching a consensus among subject experts. Conclusion: The social impact questionnaire developed consisted of 30 questions, has good internal consistency, and can be used to measure the social impact of NCDs.